THE USE OF AN INERTER FOR BASE-ISOLATION SYSTEM IN A SINGLE-DEGREE-OF-FREEDOM STRUCTURE - Predaricka Deastra (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2021)
This paper presents seismic performance of a single-degree-of-freedom (SDOF) structure equipped with a base isolation system (BIS). Common BIS employs rubber material to provide lateral flexibility in order to minimize the transmitted energy induced by the ground motion to the structure. The concept is to lower the structural natural frequency such that it falls far below the pre-dominant frequency of most earthquakes. A similar effect can also be achieved by using a device called inerter, a two-terminal device generated forces proportional to the relative acceleration between its two terminals. Instead of reducing stiffness, inerter amplifies the theoretical mass of the structure without significantly increase its physical mass. It is because, depending on the inertance-generation mechanism, an inerter is capable of generating inertance – a constant ratio of forces and relative accelerations of the inerter – several times higher than its physical mass. In this paper, the effectiveness of inerter for use as a BIS is compared to the common BIS concept. The results show that, for a similar natural frequency level, a BIS with inerter has narrower response around the resonance in the frequency domain. Furthermore, in the time domain analysis, the structure with an inerter has a lower response compared to the structure with a traditional BIS when subjected to a long-period earthquake ground motion